(untitled) (International Journal of Physiotherapy, 2014)
Background: Chronic nonspecific low back pain (CNSLBP) i.e., low back pain of at least 12 weeks duration without a specific cause is a major cause of activity limitation, absenteeism , and high health care expenses. The prevalence of CNSLBP is estimated approximately 23% and activity limitation due to LBP have been found to be 11% to 12% of the population. Previous studies comparing the efficacy of postero-anterior mobilisation and prone-press ups were done and revealed statistically significant improvements in extension ranges but not clinical relevant improvements. This is possibly attributable to single session of interventions. So long term gains in pain reduction and lumbar extension cannot be assumed. Hence this study would be intending to prove the effect of postero-anterior mobilisation and prone press ups on chronic non-specific low back pain after 6 weeks and their clinical application. Methods: 30 subjects who met the inclusion criteria were selected randomly from the department of physiotherapy, SVIMS and BIRRD, Tirupati. The study conducted for a period of 6 weeks.2 groups were formed with 15 in each group. PA lumbar glide and prone press up’s was given to group I and only prone press up’s was given to group II. Subjects were evaluated pre and post treatment for VAS, extension ROM of lumbar spine and functional disability. Result: Results showed that there exists a statistical significance between the groups in all the 3 parameters. Present randomized clinical trial provided evidence to support the use of postero-anterior mobilisation and prone press-ups in relieving pain, improving ROM and reducing disability in subjects with non-specific low back pain. In addition, results supported that postero-anterior mobilisation was more effective than prone press-ups.